Kinematically aligned total knee arthroplasty: alternative standardized technique? - Matsumoto, Tomoyuki; Takayama, Koji; Ishida, Kazunari; Hayashi, Shinya; Hashimoto, Shingo; Kuroda, Ryosuke (Annals of Translational Medicine, 2017)
Accurate osteotomy and implantation are important in total knee arthroplasty (TKA); misalignments have traditionally been reported to lead to early failure in TKA (1,2). Although the mechanical alignment method is traditionally recognized as the gold standard, kinematically aligned TKAs have recently gained a great interest for achieving better clinical outcomes (3,4). The primary goal of kinematically aligned TKA is to position the femoral and tibial components so that the angles and levels of the distal and posterior femoral joint lines and the tibial joint line are each restored to the patient’s natural alignment, avoiding a neutral limb alignment unnatural to most patients (5,6).